Pengaruh Store Ambience, Harga dan Food Quality Terhadap Keputusan Pembelian Pelanggan pada Bisnis Coffeshop - Nur Windi Nabilah; Tika Nirmala Sari (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to analyze the influence of store ambience, price, and food quality on customer purchasing decisions in coffee shops. This study uses a quantitative method with an associative approach. The research was conducted at Rahasia Coffee and Space and Katana Coffee, located in the Marelan district of Medan. The sampling technique used was purposive sampling with calculations using the Lemeshow formula, resulting in a sample size of 120 respondents. Data were collected through questionnaires distributed to customers who met the research criteria. The data was processed using SPSS software. The results of the t-test showed that for the store ambience variable, the t-value was > t-table (3.963 > 1.980), which means that the Store Ambience variable (X1) had a positive and significant partial effect on purchasing decisions (Y). The price had a t-value > t-table (2.406 > 1.980) which means that the Price variable (X2) has a positive and significant partial effect on purchasing decisions (Y), and food quality has a t-value > t-table (2.550 > 1.980), which means that the Food Quality variable (X3) has a positive and significant partial effect on purchasing decisions (Y). Furthermore, the results of the F test show that f count > f table (21.843 > 2.68) and the significance value < 0.05 (0.000 < 0.05), which means that the three independent variables, namely store ambience, price, and food quality, simultaneously influence and significant on purchasing decisions Customers of Rahasia Coffee and Space and Katana Coffee.